Radiography of the Chilean Exile through the French Office for the Refugees and Stateless People Administrative Archives - Jammet-Arias, Nathalie (Revista de Historia Social y de las Mentalidades, 2018)
From the archives of the French Office for Refugees, this article aims to show a detailed picture of the Chilean exile in France. After reminding the international conventions that regulate the issue of asylum and refuge, in the first part a typology of the Chilean exiles will be shown. It will be analyzed how they arrived in France and how they were distributed in the country. In the second part some elements on the integration at work and family way of life will highlight the tensions and the changes that the exiles tested. It contributed to create new family configurations and a redefinition of the roles within the couples. The article will conclude with some thoughts for the future of the exiles.